1998
DOI: 10.1038/sj.onc.1201890
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a p53 mutant in the epidermis of transgenic mice accelerates chemical carcinogenesis

Abstract: To develop an in vivo model for studying the role of the p53 tumor suppressor in skin carcinogenesis, a murine p53 172H mutant (equivalent to human p53 175H ) was expressed in the epidermis of transgenic mice, utilizing a targeting vector based on the human keratin 1 gene (HK1.p53 m ). HK1.p53 m mice developed normally and did not exhibit an obvious epidermal phenotype or develop spontaneous tumors. However, these mice demonstrated an increased susceptibility to a two-stage chemical carcinogenesis protocol, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 34 publications
6
50
0
Order By: Relevance
“…Previous studies (Li et al, 1998;Wang et al, 1998) have demonstrated aneuploidy in both mammary and skin tumors occurring in DMBA-treated mice carrying a targeted p53 172R-H transgene. To determine if p53 172R-H expression results in a predisposition to aneuploidy in the context of the WAP-DES transgene, FACS analysis was conducted on tumor cell nuclei.…”
Section: Mechanism Of Synergymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies (Li et al, 1998;Wang et al, 1998) have demonstrated aneuploidy in both mammary and skin tumors occurring in DMBA-treated mice carrying a targeted p53 172R-H transgene. To determine if p53 172R-H expression results in a predisposition to aneuploidy in the context of the WAP-DES transgene, FACS analysis was conducted on tumor cell nuclei.…”
Section: Mechanism Of Synergymentioning
confidence: 98%
“…Both faint and intensely stained nuclei were pooled for quantitation purposes. Quantitation of Ki 67 positive cells was conducted as described in (Wang et al, 1998). These e ects appear to be due to the gain of function properties of this p53 mutant and may be independent of direct e ects of p53 on gene transcription (Gualberto et al, 1999).…”
Section: Tumorigenesis In the Wap-des Micementioning
confidence: 99%
“…RNase protection assays (RPA) were performed using the RPA II kit (Ambion, TX, USA) and 32 Plabeled riboprobes. Riboprobe speci®c for p21 (WAF-1) was generated as previously described (Wang et al, 1998a). The SmaI/SacII fragment of murine p15 (INK4b) cDNA (kindly provided by Dr Charles J Sherr) was subcloned into pGem 5 (Promega), and linearized with ApaI as the template of the p15 riboprobe.…”
Section: Rnase Protection Assaysmentioning
confidence: 99%
“…9 Mice carrying p53 mutations analogous to the human Li-Fraumeni syndrome hot spot mutation exhibit a high incidence of spontaneous tumors with a spectrum different from that of p53-null mice, [10][11][12] a high metastatic potential for produced tumors 13 and a high incidence of chemically induced tumors. 14 Especially of note is an approach toward simulating the human context with heterozygous mice containing human p53 and Li-Fraumeni mutant p53 in the genome. 12 At the initial step of carcinogenesis caused by p53 mutation, there must exist a heterozygous state of wildtype p53 with mutant p53, resulting in the expression of both types of p53 proteins.…”
Section: Introductionmentioning
confidence: 99%